Life Significance in Maintaining Military Personnel’s Resilience: Making a Mediation Model - Savchenko, Olena; Kolesnichenko , Lina; Chuzhykova , Viktoria; Berezhenna , Olena (Insight: the psychological dimensions of society, 2024)
Crises related to the preparation and participation in combat operations negatively affect military personnel’s experience of their life significance, which in turn becomes a threatening factor in the development of negative states (anxiety, depression, stress disorders, and PTSD), and a decrease in the personal adaptive potential. The aim is to empirically test the model of relationships that predicts the peculiarities of military personnel’s coping behavior in stressful situations, where the basis (predictor) is life significance and the mediator is the clarity of self-awareness. Methods. The mediation methodology was used for non-experimental research. The study was conducted on a sample of servicemen from two companies of a separate battalion of the Armed Forces of Ukraine (n = 62) in October – November 2023. The Ukrainian-language versions of the methodologies were used: “The Perceived Life Significance Scale (PLSS)” by R. Gibberd and B. Vandenberg (Hibberd, 2016; Kolesnichenko et al., 2024), “Clarity of Self-Concept (SCC)” by J. D. Campbell et al. (Campbell et al, 1996; Kolesnichenko et al., 2024), “Instrument for the Study of Resilience (IDR-14)” by F.-W. Hu et al. (Hu, et al., 2022; Kolesnichenko & Berezhenna, 2023), “Humor Styles Questionnaire (HSQ)” by R. Martin et al. (Martin et al., 2003; Skvortsov & Zaiva, 2005). Modeling of the system “predictor – mediator – dependent variables” was carried out using SEM (Structural Equation Modeling) in the package Amos SPSS Statistics 26.0, and program “MedMod” Jamovi. Results. The model of relationships “life significance (predictor) – clarity of self-awareness (mediator) – styles of humor, manifestations of resilience (dependent variables)” was confirmed (CMIN = 13.58; df = 15; p = .905; RMSEA = .000 [.000 – .110]; CFI = 1.00; TLI = 1.01). It is predicted that aggressive and affiliative styles of humor are displayed by military personnel who experience a high level of their life significance against the background of low self-awareness. The mediator “clarity of self-awareness” determines the relationship between the level of one’s life significance and resilience. High resilience (positive thinking, belief, and hopeful mindset) is demonstrated by those military personnel who feel their life significance, have a clear self-awareness, and non-contradictory beliefs about their capabilities. Discussion and conclusions. The predicted model of the relationships “life significance (predictor) – clarity of self-awareness (mediator) – resilience, humor styles (dependent variables)” was empirically confirmed in a non-experimental study. A particularly significant role of the mediator “clear and non-contradictory self-awareness” is observed in the correlation “life significance – resilience”, since it is the level of self-awareness that is associated with cognitive coping strategies (positive thinking, belief, and hopeful mindset). The obtained relationships require verification in experimental studies.
Keywords: life significance; self-awareness; clarity of Self-concept; resilience; coping behavior; humor style; positive thinking; mediation analysis